Leveraging Instagram to Boost the Public Image of Islamic Boarding Schools - Ummi Hani'; Ummul Khoiroh; Fatimatul Husna; Holifah Holifah (Yayasan Avicenna, 2024)
This study aims to analyze the role of Instagram in strengthening the image of Islamic boarding schools in the digital era. The focus of this study is on the use of Instagram as a medium to build digital branding of Islamic boarding schools. Although many studies discuss the use of social media in education, this study offers a more in-depth approach to the strategy of using Instagram to improve the image of Islamic boarding schools. The method used is qualitative with a case study approach, which allows researchers to dig up in-depth information about the strategy and impact of using Instagram. Data were obtained through observation, in-depth interviews with the head of the Islamic boarding school, Instagram account managers, students, and the community, as well as documentation. Data analysis was carried out descriptively and qualitatively through the stages of data collection, data reduction, data presentation, and conclusion. The findings of this study indicate that Instagram is effective in presenting Islamic boarding school life, strengthening positive public perceptions, and increasing student registration. This study provides insight into the importance of implementing effective digital strategies for Islamic boarding schools so that they can be more adaptive to developments in information and communication technology and strengthen their image in the eyes of the public, especially the younger generation. Thus, Instagram can be an optimal tool to boost the image of Islamic boarding schools in the digital era.